Effectiveness of Green Mussel Shells as a Natural Coagulant for Domestic Wastewater Treatment - Ernita Sari; Ferdian Akhmad Ferizqo; Deddy Adam (Jurnal Teknokes, 2023)
Coagulation is one of the wastewater treatment processes. Aluminum sulfate is usually used as a chemical coagulant. On the other way, the use of alum can cause a new problem that was the inorganic residues produced are carcinogenic and can harm the environment and human health. Then people try to use natural materials such as chitosan as the coagulant. Chitosan can be produced from the skin of marine animals such as green mussels. This study aimed to determine the effectiveness of natural coagulant green mussel shells. The research method was an experimental study by testing the effectiveness of green mussel shells as a natural coagulant with one group post design. This research used small dose of chitosan that is 0,15 g/l until 0,4 g/l to know which one is the most effective to reduce turbidity and suspended solid. The sample in this study was domestic wastewater. The parameters were total suspended solids (TSS) and turbidity. The data were analyzed by the ANOVA test. The result showed that both TSS and turbidity were decreased by about 100% (14 mg/l to 0,65 mg/l) for optimum decreasing of TSS parameter and 73% (2.38 NTU to 0 NTU) for turbidity parameters. The optimal dose of natural coagulant green mussel shells for domestic wastewater was 0,4 g/l. The ANOVA test showed that there was an effect of green mussel shells coagulant dose on TSS and turbidity level (p-value = 0,000). The potential of using these green mussel shells as a coagulant is indeed very high. However, it takes a combination with other natural ingredients to make an effective and safe coagulant.